CONSUMPTION OF NATURAL FEED RICH IN CALCIUM AND PHOSPHORUS ON GROWTH, INTESTINAL CONDITION, AND HEPATOPANCREAS OF SAND LOBSTER (Panulirus homarus) IN PANGANDARAN REGENCY - Rostika, Rita; Haetami, Kiki; Andikawati, Aulia; Putra, Pringgo Kusuma Dwi Noor Yadi; Utama, Mochhamad Ikhsan Cahya; Wijayanti, Lady Ayu Sri; Maulida, Yulvina; Triyani, Dina Amalia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
This study aims to investigate the stimulatory effects of natural feed with calcium and phosphorus supplementation on growth and survival via physiological poses of hepatopancreas and intestine in sand lobster (Panulirus homarus). A trial was done with three types of natural feed of shell rich in calcium and phosphorus for lobsters weighing 80 g (initial weight), and that contained different mineral values: shrimp (Acetes), with calcium/phosphorus content (mg/mg) of 757/292, anchovy (Stolephorus sp) with 500/500, and golden apple snail (Pomacea canaliculata) with 129/60. This study was conducted from October 2023 to December 2023 at the KJA of the Faculty of Fisheries and Marine Science, Universitas Padjadjaran, located on the East Coast of Pangandaran Regency. The parameters measured were survival, growth, histological health of the hepatopancreas and the intestine of the sand lobsters, and water quality. The results showed the highest survival of lobsters in the treatment fed by shrimp at 96%, and the highest specific growth rate of lobsters was found in the anchovy diet at 1.90 0.5117%. Intestinal villus area of lobster was 1857.667 µm2; besides this, the histology of Hepato pancreas and intestine has been described descriptively. Water quality parameters in the research site varied as depth-visibility was from 3.1 m, temperatures of 27 to 29°C, dissolved oxygen was 6.4 to 8.8 mg/L, pH range was 7 to 8, and the salinity range was 34 to 35 ppt